Analisis Komparasi Influencer Marketing, Varian Produk, dan Keputusan Pembelian pada Menantea dan Es Teh Indonesia di Surabaya - Latifah, Laili Nur (Research Journal of Social Science and Economics, 2025)
The purpose of this study was to examine whether there are differences in influencer marketing, product variations, and purchase decisions between Menantea in Surabaya and Estée in Indonesia. This type of study is a quantitative study with a comparative approach. The study population consisted only of consumers who purchased Menantea and Indonesian estee products in Surabaya, with a total sample of 96 respondents drawn using random sampling techniques. Primary and secondary data are used as data sources. The data was collected using a closed survey-style tool and distributed via Google Forms. Collected data were then statistically processed and analyzed using SPSS 22 software to perform independent sample t-tests including variance similarity and difference tests. Results of various tests on influencer marketing variables show t-values (-1,02) < t table (2.80)). This means there is no difference between Menantea and Es Teh Indonesia in influencer marketing variables. Results of various tests on the product variant variables showed t counts (1,91) < t table (2.80)). This means that there is no difference between Menantea and Indonesian iced tea in the product variant variables. The results of various tests on the purchase decision variables show values ​​of t count (1,81) < t table (2.80). This means that there is no difference between Menantea and Es Teh Indonesia on the purchase decision variables. From this, we can conclude that there are no differences between Menantea in Surabaya and Es Teh Indonesia in influencer marketing, product variation and purchase decision variables.